A música no ensino de química: uma análise de periódicos da área - Lima, Juliana de Souza (Universidade Federal de São Carlos, 2021)
The aim of this paper is to present a literature review with a qualitative focus on music and chemistry teaching, published in the journals: Química Nova na Escola (QNEsc), REDEQUIM - Revista Debates em Ensino de Química and Educación Química en Punto de Vista. Although the few publications related to the subject, works with a theoretical approach were found, works with the first years of basic education, high school and undergraduate students. It was possible to analyze the importance that music has in the formation of children and adolescents as critical citizens and observers. We could observe that lecture classes are not the only possible means of learning. The work allows us to perceive the possibilities that the teacher has at hand when he makes proper use of this very important teaching tool.
Music and chemical education: an analysis of journals in the area
Keywords: Canções; Periódicos; Revisão bibliográfica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM